Acute macular neuroretinopathy associated with COVID-19 infection - James A. David (Elsevier, 2021)
Purpose: To report a case of bilateral acute macular neuroretinopathy (AMN) associated with a COVID-19 infection. Observations: A 22-year-old female was referred for evaluation of bilateral scotomas concurrent with a mildly symptomatic COVID-19 infection. Exam showed normal visual acuity, bilateral reddish-brown petaloid retinal lesions which were hyporeflective on near infrared (NIR) optical coherence tomography (OCT), and had associated hypoperfusion of the deep vascular plexus on OCT-angiography (OCT-A) consistent with bilateral AMN. At follow-up, scotomas and retinal findings on near infrared imaging and spectral-domain optical coherence tomography had only slightly improved. Conclusions: COVID-19 has been documented to be the etiology of a growing number of ocular manifestations including microvascular events. We report a case of bilateral acute macular neuroretinopathy in a patient with a recent diagnosis of COVID-19 infection that had persistent symptoms and findings at six month follow-up.